The impact of dysmenorrhea on the quality of life of students at a private university: a cross-sectional analysis (Research, Society and Development, 2023)
Objective: To verify the prevalence and impact of dysmenorrhea in the lives of students at a private university, in addition to comparing the intensity of the referred symptoms with the decrease in quality of life; elucidate the impact of menstrual cramps on academic absenteeism. Methods: This is a qualitative and quantitative cross-sectional study with 264 medical students enrolled in a Private University of Teresina, Piauí, to carry out the research, a self-applied questionnaire was adopted, formulated by the authors, later the data were analyzed with statistics descriptive. Results: 264 academics participated in this study with the average age of the academics who participated in the study was 23.8 years (±5.0), with a maximum age of 42 years and a minimum of 18 years. In the present study, 44.4% of the participants answered that the signs and symptoms of dysmenorrhea interfere with their usual activities in the first days. Regarding the occurrence of other symptoms, 87.5% confirmed the existence of other complaints in addition to menstrual cramps. The most prevalent symptoms were headache, nausea, diarrhea, leg pain. All participants had associated symptoms, the most common being nervous irritation (54%), breast pain (50.8%), low back pain (50.8%), headache (27.4%), nausea (26.6%), lower limb edema (13.7%), vomiting (11.3%), and diarrhea (10.5%). Conclusion: A high prevalence of dysmenorrhea was observed in this study, calling attention to a significant number of women who reported moderate to severe pain, contributing to high school absenteeism and social harm, which can negatively affect academics.